Electrocatalytic nitrate reduction to ammonia on defective Au1Cu (111) single-atom alloys - Zhang, Yuanzheng; Chen, Xiang; Wang, Weilai; Yin, Lifeng; Crittenden, John C. (Applied catalysis. B, Environmental, 2022)
Electrocatalytic reduction of nitrate (NO3–) to ammonia (NH3) in wastewater is a promising economic process for NH3 synthesis. This work designed and prepared Au1Cu (111) single-atom alloys with surface Cu vacancies (VCu-Au1Cu SAAs), which exhibited superior NH3 Faradaic efficiency (98.7%) with a production rate of 555 μg h–1 cm–2 at −0.2 V vs. RHE, while negligible activity decay was found after a durability test. Meanwhile, 97% of produced NH3 can be recovered by a simple membrane distillation. Characterizations evidence that electron migration from Cu to Au atoms creates electron-deficient Cu active sites in VCu-Au1Cu SAAs, which promote the generation of active hydrogen species (*H) that can readily hydrogenate NO3–. Theoretical calculation reveals that the bi-functional Cu sites not only promote the activation of water to produce *H but also lower the energy barrier of *NH3 desorption from the catalyst surface. [Display omitted] ●Au1Cu single-atom alloys with surface Cu vacancies (VCu-Au1Cu SAAs) is reported.●A highly NH3 Faradaic efficiency of 98.7% is obtained on the VCu-Au1Cu SAAs.●VCu-Au1Cu SAAs promoted H2O dissociation to *H that boost NO3–-to-NH3 conversion.●DFT revealed the role of single-atom and vacancy defect on catalytic performance.